CONCEPTUAL MECHANISMS THAT INFLUENCE THE LEVEL OF MOTOR ACTIVITY OF SCHOOL STUDENTS IN THE PROCESS OF ONLINE LEARNING (Physical Culture and Sport: Scientific Perspective, 2025)
Preservation and strengthening of the health of children and adolescents, formation of healthy lifestyleskills in them is the main task of the state and the education system. One of the components of a healthy lifestyle forschoolchildren is the optimal level of physical activity. The modern educational process in educational institutionsoften leads to a deterioration in the health of children and adolescents. The transition of children of different ages todistance learning technologies, according to experts, can cause adverse changes in the functional state due to a lowmotor component and significant mental stress. Such a situation requires improving the rational organization of themotor activity of children and adolescents during distance learning.The purpose of our study is to develop conceptual mechanisms that influence the level of motor activity ofschoolchildren in the process of online learning. Research methods - analysis and generalization of literary sources,questionnaires, comparative analysis, generalization. Our study used a questionnaire method to identify the mainconceptual mechanisms influencing the level of physical activity of children and adolescents in the context of onlinelearning, including organizational, psychological, social and technological. Research results: The level of physicalactivity of schoolchildren in the process of online learning is insufficient, which creates risks for their physical andmental health. The questionnaire identified key problems, including lack of motivation, insufficient integration ofphysical exercise into the educational process and low awareness of the possibilities of digital platforms fortraining. To increase the physical activity of children and young people, it is recommended to: develop active breakprograms that can be integrated into the schedule of online classes; raise awareness of students and parents aboutthe benefits of physical activity; stimulate the use of mobile applications for physical exercise through incentivesand interactive challenges; integrate elements of movement into the educational process, for example, throughgame-based classes.
Keywords: interactive challenges; online format; mobile applications; physical activity; conceptual; social; organizational; psychological mechanisms